The impact of sociodemographic factors on the self-confidence of modern students / Влияние социально-демографических характеристик на уверенность в себе современных студентов - ROSCIUPCHIN Diana 10F (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The purpose of this article is to study the impact of sociodemographic factors on the self-confidence of 1st to 3rd year college students. Also, a variety of opinions shaped by foreign authors are presented regarding the concept of "self-confidence" and what it is influenced by, resulting from the analysis of theoretical, scientific and practical literature on the research topic.